2017
DOI: 10.12944/carj.5.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Micronutrients on Plant Growth, Yield and Flower Bud Quality of Broccoli (Brassica Oleracea Var. Italica)

Abstract: A field experiment was conducted to study the “Effect of different micronutrients on plant growth, yield and flower bud quality of broccoli (Brassica oleracea Var. Italica) cv. – Green Bud” during rabi season of 2014-15 Research field, Department of Horticulture, Allahabad School of Agriculture, Sam Higginbottom Institute of Agriculture, Technology and Sciences Allahabad. The experiment consists of 10 treatment viz, T0 (control), T1 (B), T2 (Mo), T3 (Mn), T4 (B + Mo), T5 (B+ Mn +Zn), T6 (Mo +Mn), T7 (B +Mo +Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 3 publications
15
10
0
Order By: Relevance
“…T7RDF +Boric acid (B)@0.2%+ Ammonium molybdate (Mo)@0.Similar result was also observed bySingh et al (2017) …”
supporting
confidence: 81%
See 1 more Smart Citation
“…T7RDF +Boric acid (B)@0.2%+ Ammonium molybdate (Mo)@0.Similar result was also observed bySingh et al (2017) …”
supporting
confidence: 81%
“…Observations were recorded on plant height, number of leaves per plant, days to curd initiation, days to 50% curd maturity, curd diameter, curd depth, curd yield. [13] and Sitapara et al (2011) [14] in cauliflower.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, neither nitrogen levels nor micronutrient application had altered the trait of number days to maturity (Table 2) over the two growing seasons. Contrary, Singh et al (2017) reported that soil application of Borax (20 kg/ha) combined with Sodium molybdate (2 kg/ha) as sources of B and Mo, respectively, accelerated the early mature yield of cauliflower. However, insignificant effects of nitrogen, micronutrient application and their interaction on number of days to maturity might be due to its high heritability, whereas, it was reported that number of days to budding is a highly heritable trait (86 and 94%), which indicates that this trait is stable and not strongly affected by environmental factors (Yousef et al, 2015;Thorwarth et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…As a result the leaf blade fails to develop properly and only the midrib portions develop resulting sword like appearance of leaves giving whiptail symptom. (Singh et al 2017) [12] .…”
Section: Introductionmentioning
confidence: 99%